A Fatal Case of Wernicke’s Encephalopathy after Sleeve Gastrectomy for Morbid Obesity - Dimitrios K. Manatakis; Nikolaos Georgopoulos (Case Reports in Surgery)
Wernicke’s encephalopathy is an acute neuropsychiatric disorder, due to thiamine (vitamin B1) deficiency. It is traditionally described in chronic alcohol abusers; however obesity surgery is an emerging cause, as the number of bariatric procedures increases. A high index of clinical suspicion is required, since initial symptoms may be nonspecific and the classic triad of ophthalmoplegia, gait and stance disorders, and mental confusion is present only in one-third of patients. Laboratory tests can be within normal range and typical MRI brain lesions are found only in 50% of cases. Aggressive supplementation with intravenous thiamine should not be delayed until confirmation of diagnosis, as it may fully reverse symptoms, but almost half the patients will still display permanent neurological deficit. We present our experience with a fatal case of Wernicke’s encephalopathy, following laparoscopic sleeve gastrectomy for morbid obesity.